2015
DOI: 10.1002/jcb.25154
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Dynamin‐Related Protein 1 in Hypoxia‐Induced Pulmonary Vascular Angiogenesis

Abstract: Pulmonary arterial hypertension (PAH) is a lethal disease characterized by pulmonary vascular obstruction due in part to excessive pulmonary artery endothelial cells (PAECs) migration and proliferation. The mitochondrial fission protein dynamin-related protein-1 (DRP1) has important influence on pulmonary vascular remodeling. However, whether DRP1 participates in the development and progression of pulmonary vascular angiogenesis has not been reported previously. To test the hypothesis that DRP1 promotes the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Fission, on the other hand, is a key factor in vascular sprouting. In pulmonary ECs, DRP-1 activation, which induces mitochondrial fission, stimulates angiogenesis by promoting proliferation, migration, and inhibition of apoptosis in a mitochondrial Ca 2+ -dependent manner [19], [21]. A defective mitochondrial network is observed in several pathological settings, such as high glucose and ischemia-reperfusion, and also during EC aging, highlighting the importance of the fusion/fission cycle during disease development [22], [23], [24], [25].…”
Section: Mitochondria In Endothelial Cellsmentioning
confidence: 99%
“…Fission, on the other hand, is a key factor in vascular sprouting. In pulmonary ECs, DRP-1 activation, which induces mitochondrial fission, stimulates angiogenesis by promoting proliferation, migration, and inhibition of apoptosis in a mitochondrial Ca 2+ -dependent manner [19], [21]. A defective mitochondrial network is observed in several pathological settings, such as high glucose and ischemia-reperfusion, and also during EC aging, highlighting the importance of the fusion/fission cycle during disease development [22], [23], [24], [25].…”
Section: Mitochondria In Endothelial Cellsmentioning
confidence: 99%
“…Marsboom et al demonstrated that inhibition of HIF-1α or Drp1 reduces proliferation in pulmonary artery smooth muscle cells, suggesting that mitochondrial fragmentation can promote proliferation [147]. Furthermore, hypoxia induced fission may contribute to angiogenesis, as Drp1 was shown to mediate hypoxia-induced increases in pulmonary microvessels, and knockdown of Drp1 decreases CD31-positive blood vessels in a Ras-driven xenograft model [61,150]. In addition to these hypoxia-induced changes, HIF-1α has been shown to cooperate with other signaling nodes to promote pro-tumorigenic physiological changes.…”
Section: Hypoxic Signalingmentioning
confidence: 99%
“…While several studies have reported that ischemia reperfusion-induced mitochondrial fission is associated with decreased ROS production and apoptosis in neuronal cells and cardiomyocyte [ 15 16 21 ], little is known about the effect of mitochondrial dynamics on angiogenesis. As hypoxia is known to affect both angiogenesis and mitochondrial function, we examined that the effect of mitochondrial dynamics on angiogenesis [ 22 ]. In agreement with our results, Zhao et al confirmed that DRP1 plays critical roles in cell migration and invasion in breast cancer under hypoxic condition [ 23 ].…”
Section: Discussionmentioning
confidence: 99%